TINDAK TUTUR DIREKTIF DALAM DIALOG FILM SURGA YANG TAK DIRINDUKAN I - Dwikurniasari, Septi Arsista; Saman, Sisilya; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe researcher decided to choose The Directive Speech Act as the main focus of the reseach; it is kind of speech that more often found in the daily life. The problem being discussed in this research are context, purpose, and type of the directive speech act in the movie entitled Surga yang Tak Dirindukan I, as well as the implementation in teaching and learning process in school. The research methods used by the reasearcher are data collection, validation, and data analysis. The result of directive speech act analysis from the movie SYTD I are: dicrective speech act of requesitives, which are the acts of requesting, begging, inviting, and stressing; dicrective speech act of question which is the act of asking; dicrective speech act of requirements which are the acts of ordering, directing, and commanding; dicrective speech act of prohibitives consists of the acts of prohibiting and limiting; dicrective speech act of permissives consists of the acts of granting and forgiving; dicrective speech act of advisories consists of the acts of reminding, suggesting and advising. The analysis result of the directive speech act can be applied in a learning process in school as a model of the drama text. Keywords: The Directive Speech Act, The Dialogue of The Movie, Surga yang Tak Dirindukan